2019
DOI: 10.1186/s40795-019-0280-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying perceived barriers and enablers of healthy eating in college students in Hawai’i: a qualitative study using focus groups

Abstract: Background: To design effective nutrition education interventions for college students, research is needed to determine the factors influencing food choices. The purpose of this study was to identify perceived barriers and enablers of healthy eating in college students ages 18-24 at the University of Hawai'i at Mānoa. Methods: Prior to conducting focus groups, an interview guide was developed based on a literature review of relevant studies. The interview guide was successfully tested in the first focus group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 33 publications
(39 reference statements)
4
29
0
Order By: Relevance
“…This study proved that there are statistically significant relationships between understanding of the concept of a healthy diet and marital status, BMI, and education about food and nutrition, indicating that the students who understand the meaning of a healthy diet tend to be single, with a normal BMI, and have received nutritional education. Studies have shown that most students are not acquainted with necessary healthy foods of different categories and are in need of educational programs about healthy food and nutrition [19,24,40]. This is in line with a cross-sectional study conducted at Kuwait University to assess the body mass index, eating habits, attitudes, calculation of healthy eating scores, and gender differences among these domains.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This study proved that there are statistically significant relationships between understanding of the concept of a healthy diet and marital status, BMI, and education about food and nutrition, indicating that the students who understand the meaning of a healthy diet tend to be single, with a normal BMI, and have received nutritional education. Studies have shown that most students are not acquainted with necessary healthy foods of different categories and are in need of educational programs about healthy food and nutrition [19,24,40]. This is in line with a cross-sectional study conducted at Kuwait University to assess the body mass index, eating habits, attitudes, calculation of healthy eating scores, and gender differences among these domains.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, in most cases, students preferred to take snacks as their breakfast and lunch, and preferred to buy these snacks from restaurants or the university cafeteria [20]. A similar study evidenced that most students (83.6%) regularly eat three meals per day and understand the concept of a balanced diet, but only 7% follow this for their own diet, yet 51% showed a tendency towards learning more about healthy diets [24].…”
Section: Discussionmentioning
confidence: 85%
“…A healthy lifestyle lowers CVD risk by 50% for high genetic risk persons and prolongs life expectancy [ 4 , 5 ]. The practice and adherence of a healthy lifestyle are affected by various factors such as; individual’s beliefs, attitudes, knowledge, cultural issues, accessibility, availability, affordability, parental support, income, peer pressure, institutional/physical environment (neighborhoods, worksites, and schools), regulations, policies (local, state, and federal), health care provider counseling, absence of sign and symptoms, stress/anxiety, and social media [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Achieving health promotion in college students is rather challenging for at least four reasons. First, the on‐campus environment exposes college students to many hazardous habits, such as abusive drinking (Lorant, Nicaise, Soto, & d’Hoore, 2013) and unhealthy eating (Amore, Buchthal, & Banna, 2019). Second, the developmental transition into college leads to a decline in psychological well‐being and psychological distress that is higher than the distress experienced by nonstudents (Bewick, Koutsopoulou, Miles, Slaa, & Barkham, 2010; Conley, Kirsch, Dickson, & Bryant., 2014).…”
Section: Introductionmentioning
confidence: 99%